INGKAR JANJI UNTUK MENIKAH DALAM PRESPEKTIF PASAL 1365 KUHP DAN HADIST RIWAYAT BUKHARI DAN MUSLIM - Lutfi Hasbullah; Tajul Arifin (Tashdiq: Jurnal Kajian Agama dan Dakwah, 2024)
The act of breaking a promise to marry often occurs in society recently, so that many victims feel very disadvantaged, not only losing materially but also immaterially. This has led to many cases being sued in court. The purpose of this study is to find out how the views of civil law and Islamic law regarding the act of breaking a promise to marry, whether the act is an unlawful act or an act of default, then what are the sanctions given by law for this action. Then the method used is literature and a qualitative approach where a qualitative approach is carried out based on the phenomena that occur. This study uses a descriptive analytic research type, namely research by collecting data then the data is compiled, analyzed, then conclusions are drawn. By providing a clear and systematic description of the act of breaking a promise to marry in terms of civil and Islamic law. The results of the study are that breaking a promise to marry is an unlawful act, not an act of default because it fulfills the elements of Article 1356 of the Civil Code, and is also said to be an unlawful act because it has violated the norms of decency and decency in society. The legal consequences obtained for having committed an unlawful act are compensation for costs, losses and interest to the victim. In Islamic law, the cancellation of the khitbah is permissible as long as it is done with rational reasons and in a good way, but if an act of breaking a promise is made causing the khitbah to be canceled it is not permissible because it will cause social problems, namely slander and ongoing conflict.